FIVE FINGERS HYPNOSIS TO REDUCE ANXIETY AMONG STUDENTS BEFORE THESIS EXAMINATION - Novi Rahma Ningrum; Syadam Rizky Pahlevi, Muhammad; Purnama, Heni (Rifapublisher.id, 2024)
Background: Anxiety is a very natural thing for anyone, including students during their final assignments who often feel worry, nervousness and confusion before examination. Objective: This study aims to determine the effect of Five Finger Hypnosis to reduce anxiety among students who are going to thesis exams. Methods: This research was a quasy-experimental study with a one group pretest posttest approach, a total sample was 40 respondents at STIKep PPNI West Java Campus. The sample was selected by using the Accidental Sampling technique and data collection using the State – Trait Anxiety Inventory (STAI) questionnaire. The data analysis was used Paired T-test. Results: Univariate analysis showed that 22 respondents had moderate anxiety (84.6%) during the pretest, and 15 people had mild anxiety (57.7%) and 11 respondents had moderate anxiety (42.3%) during the posttest. Bivariate analysis showed that there was significant effect of Five Finger Hypnosis on anxiety in students who were about to take thesis exams with a value of t = -7,324, sig = 0.000 (p <α 0.05). Conclusion: In this study, five finger hypnosis had a strong effect on students when facing the thesis proposal exam before and after the intervention.